Agglomerate size evolution in modular twin‐screw extruder: Modeling and validation with CaCO3/LLDPE compounding experiments. Issue 47 (26th July 2017) - Chen, Tao; Lin, Hua; Zhao, Haili; Chen, Xin; Wu, Tong; Li, Guo; Ji, Huajian; Sha, Jin; Ma, Yulu; Xie, Linsheng
ABSTRACT: The screw combination of twin‐screw extruder affects the filler size in inorganic filler‐reinforced polymeric compounds. This article tried to conveniently and precisely model the agglomerate size evolution in modular co‐rotating twin‐screw extruder. The break‐up process of agglomerate was analyzed to obtain the relationship between average deagglomerating energy ( M ) and agglomerate size, the result presented a mathematic relationship between M and agglomerate size. Numerical simulation study was conducted to consider the effect of kneading blocks (KB) or flight elements (FE) number on dispersion capacity of screw combination. The average deagglomerating energy, calculated based on POLYFLOW simulation, was introduced as major parameter to evaluate the dispersion capacity, which presented a proportional relationship to the KB or FE number. The model was developed by combining the agglomerate break‐up process and simulation results. In validation, CaCO3 /linear low‐density polyethylene (LLDPE) compounds were prepared by modular co‐rotating twin‐screw extruder with different screw combinations. The optical image analysis showed that CaCO3 agglomerate size decreased with the KB or FE number rising, while it achieved minimum when the KB number was 4. The model was in accordance with the experimental results, and proved to be valid for KB and FE combinations in preparing CaCO3 /LLDPE compounds. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45535. Abstract :